Edge : Leadership Secrets from Footballs?s Top Thinkers - Lyttleton, Ben
In Edge, Ben Lyttleton gets unprecedented access to some of the world's top football clubs to discover their innovative methods for developing talent and reveals how we can use them in our everyday lives. Elite teams now look for an edge by improving